PENGARUH WAKTU KONTAK TERHADAP PENJERAPAN EKSTRAK ETANOL PUCUK DAUN PUCUK MERAH (Syzygium oleana) OLEH KERTAS SARING - Sukemi Sukemi (PROSIDING SEMINAR KIMIA, 2020)
This study aimed to determine the effect of contact time on % adsorption of ethanol extract of Pucuk Merah (Syzigium oleana) Shoot-Leaves (PMSL) by filter paper. The ethanol extract of PMSL was obtained by using maceration technique for 24 hours with material liquor ratio (MLR) of 1:7 (g/ml). The adsorption of ethanol extract of PMSL onto filter paper was done at different contact times, i.e. 30, 60, 90, and 120 minutes with MLR of 1:100 (g/ml), filter paper weight of 0.2850 Â± 0.0092 g, solution volume of 30 ml and temperature of 81oC. The results showed that contact time effect on adsorption of ethanol extract of PMSL onto filter paper. The % adsorption of ethanol extract of PMSL onto filter paper increased with an increase in the contact time. The optimum contact time on the adsorption of ethanol extract of PMSL by filter paper was 90 minutes. Keyword : Pucuk merah shoot-leaves, Syzigium oleana, contact time, adsorption.